A knowledgebase web platform for collaborative physical system modeling and simulation - Zhang, Yanshan (2014)
Engineering study involves concepts, principles and phenomena that are difficult to interpret due to people’s cognitive constraints. Learning through experiments is acknowledged to be one of the most effective ways of gaining new knowledge. Computer simulation involves applying scientific theories and performing data analysis on the collected data. Many simulation platforms provide visualization tools for observing phenomena and data analysis, and these are all characteristics of experiments. Hence, computer simulation can be used as a complementary tool to understand concepts, principles and phenomena other than actual physical experiments.